Children in special care and detention : someone else's problem - Young, Siobhan (Trinity College (Dublin, Ireland). School of Social Work and Social Policy, 2014)
Detaining children has a long and turbulent history in Ireland as the publication of the Commission to Inquire into Child Abuse Report demonstrated in 2009. This was the result of a 10 year inquiry into the industrial and reformatory school system which detained thousands of children. Today, the legislative and policy emphasis is on the principle of detention as a last resort and consequently only a small number of children are detained. This thesis aims to enhance our understanding of the purpose and function of the contemporary institution by examining professional constructions of children confined there. The study focuses on two sites, special care units where children are deemed to require detention for 'welfare' reasons and children detention schools where children are detained for reasons of 'criminality'. It is the first study to include empirical data from both settings and therefore adds to the limited research in this area. In order to fully appreciate the present of organisations, it is useful to understand how history and social policy have shaped them. The literature indicates that there are two dominant themes that explain the purpose of reformatory and industrial schools. -- 1. The schools represented a progressive improvement on previous systems that had not considered childhood as a vulnerable period. -- 2. They represented an expansion of state and professional control over the behaviour of working class families.
Keywords: Social Work and Social Policy, Ph.D.; Ph.D. Trinity College Dublin